2020
DOI: 10.1002/joc.6641
|View full text |Cite
|
Sign up to set email alerts
|

Regional variability in lightning activity over South Asia

Abstract: The regional variability of lightning activity over 10 different regions, selected with at least one major meteorological/topographical feature, of South Asia (8 N-36 N, 90 E-100 E) have been examined on all time scales from the data obtained from July 1995 to December 2013 from the Tropical Rainfall Measuring Mission satellite. A comparative study of the correlation coefficients calculated between lightning flash rate and convective parameters, aerosol optical depth (AOD) and topography for different regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…It is interesting to note that during JJAS, the combined correlation coefficient over Region 2 is significantly high ( R ∼ 0.8). However, the correlation value over Region 2 is less during MAM ( R ∼ 0.42) than in the other regions, which might be related to orography, as Kamra and Ramesh Kumar (2020) highlighted. They reported that the Himalayas over the North‐West (Region 2) region play a crucial role in lightning activity due to solar heating and moisture availability.…”
Section: Resultsmentioning
confidence: 98%
“…It is interesting to note that during JJAS, the combined correlation coefficient over Region 2 is significantly high ( R ∼ 0.8). However, the correlation value over Region 2 is less during MAM ( R ∼ 0.42) than in the other regions, which might be related to orography, as Kamra and Ramesh Kumar (2020) highlighted. They reported that the Himalayas over the North‐West (Region 2) region play a crucial role in lightning activity due to solar heating and moisture availability.…”
Section: Resultsmentioning
confidence: 98%
“…Aerosol optical depth (AOD) of 550 nm with 1 • x1 • grid resolution data is retrieved from Moderate Resolution Imaging Spectroradiometer (MODIS)T(https://giovanni.gsfc.nasa.gov/giovanni)for the period 2018 -2021. More details of different region of India & World (13,15)…”
Section: Data-setsmentioning
confidence: 99%
“…CAPE is a measure of buoyancy force, which plays an important role in determining vertical updraft velocity. CAPE is dominating over the northeast region as well it is strongly impacted by the progress of the monsoon (13) . In the Himalayan region, CAPE and surface temperature are responsible for the instability (50-60 % relative humidity at 700 hpa) and lead to an ideal condition for intense lightning (14) .…”
Section: Introductionmentioning
confidence: 99%
“…The advection of moisture laden south‐west monsoon winds, heated land surface (Kamra & Ramesh Kumar, 2021) accompanied by strong updrafts across complex topography (Vishnu et al., 2013) are the major causes of lightning over the mesoscale mountain ranges of Western Ghats (WG). In a case study approach, Mudiar et al.…”
Section: Introductionmentioning
confidence: 99%
“…The advection of moisture laden south-west monsoon winds, heated land surface (Kamra & Ramesh Kumar, 2021) accompanied by strong updrafts across complex topography (Vishnu et al, 2013) are the major causes of lightning over the mesoscale mountain ranges of Western Ghats (WG). In a case study approach, Mudiar et al (2018) utilized lightning network observations to delineate the presence of higher concentration of bigger raindrops in strongly electrified storms owing to enhancement in collision-coalescence processes over the WG.…”
mentioning
confidence: 99%